STORYLINE OF BATEE MEUCANANG FOLKLORE (STUDY FACTUAL STRUCTURE) - Lina Sundana (Jurnal Disastri (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2023)
This study aims to describe the flow and plot of the Acehnese folklore Batee Meucanang using a factual structural study of literary works. This story is an Acehnese oral literature originating from South Aceh with the type of Legend story. The factual structure consists of story facts, themes and story tools that can be found in the plot and plot as the focus of the problem in this study. This research method uses this type of research is a qualitative research. The data source in this study is the Acehnese folklore Batee Meucanang. while the data from this study are part of the text that shows the plot and plot of the story. Data collection technique is done by documentation study. The data analysis method used is the content analysis method. The results of the study found 13 plots and plots consisting of 10linear sequences and flashback sequences.